(untitled) (Homoeopathy for All, 2025)
Acne is one of the most common dermatological conditions affecting adolescents and adults alike, often impacting physical appearance, self-esteem, and quality of life. It is often considered as a cosmetic concern. The complex interplay of genetics, temperament, digestive and hormonal equilibrium, and mental state underlies the visible eruptions such as papules, pustules, and cysts. Conventional perspectives emphasise hormonal, dietary, and microbial factors; however, the complexity of acne transcends these superficial explanations. Conventional therapeutic guidelines recommend the use of topical and oral retinoids, antibiotics, benzoyl peroxide, azelaic acid, chemical peels, and light therapy, among other treatments. Patients have progressively begun exploring complementary and alternative medicine (CAM) options, including homeopathy., , Worldwide, homeopathy is considered the second most prevalent kind of complementary and alternative medicine utilised by outpatient dermatology patients, with acne being the most often treated condition through CAM therapy. Evidence indicates that homeopathy can enhance the condition of acne and its associated scars, hence justifying treatment for these patients. Patients are increasingly seeking therapies that they believe provide relief with minimal adverse effects, for which homeopathy is renowned.